2001
DOI: 10.1038/sj.onc.1204398
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional domains involved in BTG1 cell localization

Abstract: We have previously shown that BTG1 stimulates myoblast di erentiation. In addition, this protein displays a major nuclear localization in con¯uent myoblasts, decreasing during the early steps of di erentiation, and is essentially detected in the cytoplasm of mature myotubes. To identify the domains involved in the cellular tra cking of BTG1, we observed the localization of several BTG1 sequences fused to bGalactosidase. The highly conserved B box among all members of the BTG family induces a signi®cant nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…The highly conserved B box of BTG1 induced significant nuclear localization of h-galactosidase; it was enhanced by the presence of the COOH-terminal moiety. Moreover, the NH 2 -terminal LxxLL motif of BTG1, which mediates interaction with members of the nuclear receptor superfamily, also favored nuclear localization (31). The domains of BTG2 required for directing nuclear localization are consistent with these observations; the conserved boxes B and C of BTG1 and BTG2 share 100% and 80% homology, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…The highly conserved B box of BTG1 induced significant nuclear localization of h-galactosidase; it was enhanced by the presence of the COOH-terminal moiety. Moreover, the NH 2 -terminal LxxLL motif of BTG1, which mediates interaction with members of the nuclear receptor superfamily, also favored nuclear localization (31). The domains of BTG2 required for directing nuclear localization are consistent with these observations; the conserved boxes B and C of BTG1 and BTG2 share 100% and 80% homology, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…We also reported that BTG1 is submitted to cellular trafficking and that T3 increases the nuclear localization of the protein. Interestingly, whereas a BTG1 mutant located in the cytoplasm is devoid of any myogenic activity, a mutant displaying major nuclear localization increases myoblast withdrawal from the cell cycle and stimulates myoblast differentiation (Rodier et al, 2001). These data established that BTG1 exerts its myogenic influence at nuclear level, and is a T3 target involved in the control of myoblast differentiation by the hormone .…”
Section: Introductionmentioning
confidence: 65%
“…In addition, we provided evidence that BTG1, submitted to cell trafficking, exerts its myogenic activity at nuclear level (Rodier et al, 2001). These data led us to As the protein displayed two LxxLL motifs considered to be involved in the interaction of coactivators with nuclear receptors (Heery et al, 1997), we privileged the possibility that BTG1 could act as a coactivator of several transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclin-dependent kinase p34cdc2, in complex with either cyclin E or cyclin A, was shown to phosphorylate BTG1 on serine 159, facilitating the interaction of BTG1 with the human carbon catabolite repressor protein -associative factor 1 (29). Phosphorylation promoted the nuclear localization of BTG1, blocking cellular proliferation and resulting in growth inhibition (29,30). In addition, the Forkhead transcription factor FoxO3a was shown to directly induce the btg1 promoter, up-regulating the expression of BTG1 and stimulating differentiation of erythroid cells (20).…”
Section: Discussionmentioning
confidence: 99%